Treatment Options for Cystic Fibrosis: State of the Art and Future Perspectives - H. Sears, Edmund; J. Gartman, Eric; P. Casserly, Brian (Reviews on Recent Clinical Trials, 2011)
Cystic fibrosis (CF) is an autosomal recessive disorder characterized by chronic lung and sinus disease, impaired mucociliary clearance (leading to recurrent pulmonary infection), pancreatic insufficiency, elevated sweat chloride levels and male infertility. Cystic fibrosis transmembrane conductance regulator (CFTR) is a cAMP-regulated chloride channel in the plasma membrane of epithelial cells lining the lung, pancreas, liver, intestines, sweat duct, and the epididymis. Genetic mutations in CFTR affect its synthesis, processing, and transport to the plasma membrane and/or impede its function as a chloride channel and conductance regulator. Research is proceeding on multiple fronts including inhalational agents, anti-inflammatory treatments, and pancreatic replacement therapies. Furthermore, improved understanding of the molecular mechanisms that lead to CFTR dysfunction has stimulated the design of therapeutic strategies aimed at restoration of CFTR function, or “protein repair therapy”. Recent clinical trials have shown these interventions have the ability to restore some level of CFTR function in vivo. This review will provide an overview of recent clinical trials that investigate new therapeutic approaches in CF designed to treat chronic respiratory infection, reduce inflammation, and improve pancreatic enzyme supplementation as well as trials addressing the greatest therapeutic challenge - restoring the function of the CFTR protein.
Keywords: therapeutic options